Pembangunan Ekonomi Berkelanjutan sebagai Kepentingan Nasional Indonesia dalam Presidensi G-20 - Solechah, Warhidatun Maratus; Sugito, Sugito (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
The Group of Twenty (G20) is an international economic forum that focuses on solving challenges to global economic growth, including issues of trade, investment, finance, infrastructure, employment, corruption eradication, development, agriculture, technology, energy, innovation, and the economy. digital. In the current leadership period, Indonesia was elected as the G20 Presidency in 2022. This study uses a qualitative research method with a literature study approach with the aim of analyzing Indonesia's national interests in the G20 Presidency. The data sources of this study used primary data in the form of official government documents and reports and secondary data in the form of journal articles and online media news. The data obtained in this study were further reduced and analyzed. The results of this study indicate that Indonesia utilizes the G20 forum to achieve its national interests through multilateral meetings in various international and regional forums, such as the Inter-Parliamentary Union (IPU) and the Asia Pacific Parliamentary Forum (APPF) as well as promoting economic cooperation to deal with dominance of a large country or certain regional groups such as the United States and the European Union.